Battling Covid-19 with Artificial Intelligence: What Will Work in Africa? - Abejide Ade-Ibijola and Charis Harley (The Thinker, 2020)
Many researchers and industry experts working in Artificial Intelligence (AI) have claimed that AI holds the answers to the past, present, and future difficulties faced by mankind. We form part of this group, and with the coming of Covid-19 – a pandemic which is raging through the world and has so far claimed over 300,00 lives – we argue that now is the time to combine human ingenuity with the capability of machines to support a world in crisis. It has been predicted that Covid-19 will result in a high death toll in Africa, as has been the case on other continents. Vaccines and/or a cure will take more than a year to be realised, hence the question: can we turn to technology, specifically AI, for a solution? In this article, we consider the context of Africa in particular, our specific difficulties, and how AI can help Africa in the fight against Covid-19. The goal is to curb its spread, help predict patterns of spread, support social distancing measures, help in contact tracing, and assist with reopening economies. A key point in this article is that not all AI technologies are feasible within the African context, not only because of affordability concerns, but also because of current policies and social contexts.